2018
DOI: 10.1158/1538-7445.sabcs17-p5-21-11
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-21-11: Benefit from palbociclib and fulvestrant based on previous fulvestrant and/or everolimus treatment. Based on a cohort of over 200 patients treated in a French compassionate program

Abstract: Background: CDK4/6 inhibitors have been approved in the recent years for the treatment of advanced hormone receptor-positive breast cancer. For patients with resistance to previous endocrine therapy, the approval is based on the results of the PALOMA-3 trial testing palbociclib in addition to fulvestrant observing a progression-free survival (PFS) of 9.2 months. Nevertheless, in this study no previous treatment with fulvestrant was allowed and no information had been reported of efficacy after everolimus admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…In two previous compassionate use programmes, no differences in median PFS were observed in patients receiving palbociclib following fulvestrant and/or everolimus. 45,46 This is consistent with our results: in the subgroup analysis, 32.4% of patients pretreated with everolimus/exemestane and 35.5% of patients previously treated with fulvestrant obtained an objective response, reinforcing recent suggestions that palbociclib could reverse the acquired resistance to ET. 9,47,48 A more recent trial on 60 everolimus-pretreated patients reported a median PFS of 5.8 months in the whole population and 6.4 months in 48% of patients also receiving fulvestrant as previous treatment line.…”
Section: Discussionsupporting
confidence: 92%
“…In two previous compassionate use programmes, no differences in median PFS were observed in patients receiving palbociclib following fulvestrant and/or everolimus. 45,46 This is consistent with our results: in the subgroup analysis, 32.4% of patients pretreated with everolimus/exemestane and 35.5% of patients previously treated with fulvestrant obtained an objective response, reinforcing recent suggestions that palbociclib could reverse the acquired resistance to ET. 9,47,48 A more recent trial on 60 everolimus-pretreated patients reported a median PFS of 5.8 months in the whole population and 6.4 months in 48% of patients also receiving fulvestrant as previous treatment line.…”
Section: Discussionsupporting
confidence: 92%
“…The range of median PFS for palbociclib plus fulvestrant across all lines of treatment in RWE studies was 5.46-13.3 months, which was overall comparable to 11.2 months observed in the PALOMA-3 clinical trial [19]. The lower end of this range (5.46 months) was also from a study that included heavily pretreated patients [36]. However, follow-up period for most studies remained low.…”
Section: Discussionsupporting
confidence: 52%
“…Almost a half of them received more than 6 lines, 48% of these patients had previously been treated with fulvestrant and 67.8% with everolimus in combination with ET. The median PFS of patients treated with fulvestrant and palbociclib was 5.46 months, with no significant differences between patients pretreated with fulvestrant or everolimus in univariate analysis (Arnedos et al, ). Within a compassionate use program, another single‐centre retrospective analysis of 34 heavily pretreated patients showed a disease control rate of 52.9% at Week 12 and 24.4 at Week 24, and a PFS of 3.1 months, with no significant difference between everolimus‐pretreated (3.5 months) and everolimus‐naïve patients (2.7 months; Maurer et al, ).…”
Section: Discussionmentioning
confidence: 99%